Magnetic fluid hyperthermia for bladder cancer: A preclinical dosimetry study. (19th September 2013) - Oliveira, Tiago R.; Stauffer, Paul R.; Lee, Chen-Ting; Landon, Chelsea D.; Etienne, Wiguins; Ashcraft, Kathleen A.; McNerny, Katie L.; Mashal, Alireza; Nouls, John; Maccarini, Paolo F.; Beyer, Wayne F.; Inman, Brant; et al.
Abstract: Purpose : This paper describes a preclinical investigation of the feasibility of thermotherapy treatment of bladder cancer with magnetic fluid hyperthermia (MFH), performed by analysing the thermal dosimetry of nanoparticle heating in a rat bladder model. Materials and methods : The bladders of 25 female rats were instilled with magnetite-based nanoparticles, and hyperthermia was induced using a novel small animal magnetic field applicator (Actium Biosystems, Boulder, CO). We aimed to increase the bladder lumen temperature to 42 °C in <10 min and maintain that temperature for 60 min. Temperatures were measured within the bladder lumen and throughout the rat with seven fibre-optic probes (OpSens Technologies, Quebec, Canada). An MRI analysis was used to confirm the effectiveness of the catheterisation method to deliver and maintain various nanoparticle volumes within the bladder. Thermal dosimetry measurements recorded the temperature rise of rat tissues for a variety of nanoparticle exposure conditions. Results : Thermal dosimetry data demonstrated our ability to raise and control the temperature of rat bladder lumen ≥1 °C/min to a steady state of 42 °C with minimal heating of surrounding normal tissues. MRI scans confirmed the homogenous nanoparticle distribution throughout the bladder. Conclusion : These data demonstrate that our MFH system with magnetite-based nanoparticles provides well-localised heating of rat bladder lumen with effective control of temperature in the bladder and minimal heating of surrounding tissues.